Спорные вопросы приобретения права собственности на клад - Bystrowa, Maria (Europejskie Stowarzyszenie Studentów Prawa ELSA Poznań, 2014)
The study aims at an evaluation of the acquisition of the ownership of the treasure in the civil law of the Russian Federation. The author presenting the selected controversial issues according to the acquisition of the ownership of the treasure focus on its practical dimension with a special emphasis on the cultural heritage.
Controversial issues in the context of the acquisition of the ownership of the treasure
Keywords: ownership of the treasure; cultural heritage; civil law